Preschooler’s Cognitive Development in Correlation with Their Parents’ Implicit Theories of Intelligence and Personality - Vindeker, O; Pavlova, S (KnE Life Sciences, 2018)
This paper is devoted to cognitive development of preschoolers in correlation with implicit theories of their parents. There are four positive mindsets of intelligence and learning motivation: (1) growth intelligence mindset, (2) growth personality mindset, (3) acceptance of learning goals, (4) positive learning self-esteem. We hypothesized that cognitive and intellectual parameters and self-esteem of preschoolers correlate with parents’ growth mindsets. The study involved 120 subjects-40 preschoolers in age of 6 ± 0.5 years old (20 boys and 20 girls) and their 80 fathers and mothers. The parents ’ sample consisted of subjects aged from 27 to 54 years average age was 37.9 ± 6.7 years old). To investigate the cognitive differences of preschoolers we used: (1) two subtests of WISC (for examining attention and short-term memory); (2) Method of Verbal Thinking of Kern-Yirasek; (3) Method of Express Diagnostics of Intellectual Abilities (MEDIA) I. S. Averina, E. I. Shabanova and E. N. Zadorina. To explore parents’ mindsets Questionnaire of Implicit Theories of Intelligence and Personality (by C. Dweck, in the adaptation of T.V. Kornilova et al, 2008) was used. It was determined that the indicators of cognitive development and intelligence of girls are more related to parental attitudes than boys. In this case, the closest relationship is observed in the dyad ”father – daughter”. Indicators of attention, short-term memory, understanding of quantitative and qualitative relations, logical thinking are associated with mindsets of growth intelligence and adoption of their fathers’ high learning value. Girls ’mathematical abilities are positively related to fathers’ and negative mothers ’ growth mindsets. Keywords: parents’ influence, growth intelligence mindset, growth personality mindset, learning goals, learning self-esteem, cognitive and intellectual development.